The curriculum : theory and practice - Kelly, A. V. 4 0 (Albert Victor)16; 5 (Los Angeles : SAGE, 2009)
Examines the philosophical and political aspects of curriculums--with a focus on England, Wales, and the United States--and explains curriculum theory, five key elements of an educational curriculum, and ways to incorporate them to reflect a democratic society.
Includes bibliographical references and indexes.
Professional.
Keywords: 2 -- 0; 6; Curricula. -- Education;Curriculum planning. -- 20; 20; 2